Phrases of Maybrat - Lulu Jola Uktolseja; Sherly Gaspersz (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
The objectives of the study are to describe (1) Attributive endocentric phrases, (2) Appositive endocentric phrases, (3) Coordinative endocentric phrases, and, (4) Exocentric phrases. The research methodology used in this research is qualitative descriptive method. Techniques for collecting data in this research are the observation and interviewing the informants. In analyzing the data, the researcher used the tagmemic methods. The informants of this research are the people of Maybrat region who lived in Jl. Tanjung Dofior Belakang Unamin. The informants have fulfilled the requirements given by the researcher. The approach used in this study was bilingual approach, instead of monolingual approach, that is, by asking the informants to translate the words (phrases) from Bahasa Indonesia to Maybrat language. The result of this research is the phrase of Maybrat language divided into two kinds as general, they are endocentric and exocentric phrase. It is also classified into noun phrase, pronoun phrase, verb phrase, adjective phrase and pre(post) position phrase. Each phrase has its own pattern. Some of them are similar into English and Indonesian, but some are really different.